Toward Sustainable Use of Space: Economic, Technological, and Legal Perspectives. (August 2021) - Palmroth, M.; Tapio, J.; Soucek, A.; Perrels, A.; Jah, M.; Lönnqvist, M.; Nikulainen, M.; Piaulokaite, V.; Seppälä, T.; Virtanen, J.
Abstract: During the last few years, the amount of space debris has been frequently mentioned as a potential risk to current and future space operations. The purpose of this article was to describe the discussions held at the First Sustainable Space Economy Workshop held in Finland 2019. The workshop gathered together experts with economic, legal, regulatory, technological, and environmental backgrounds, with an aim of discussing the sustainable use of space from all these perspectives. As an outcome of these discussions, we find that two concepts, satellite sustainability footprint and orbital capacity, should be introduced at an international level. The satellite sustainability footprint measures how likely the satellite stays healthy and operating, without causing risks to self or others. The orbit capacity is essentially an integral of the footprint over an orbit, and it determines how many satellites of different footprints could be launched to the same orbit. In addition, in this article, we discuss how to realize such concepts within the current normative framework. The authors suggest both top-down and bottom-up approaches, necessitating negotiations within an intergovernmental framework and with the relevant space actors. The most important finding of the workshop and this article, however, is that different space-related fields and experts having diverse backgrounds should continuously discuss in a constructive and informal manner to realize the sustainable utilization of space in practice.